2010
DOI: 10.1158/0008-5472.can-10-2465
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression Network Analysis Identifies Transcriptional Modules Related to Proastrocytic Differentiation and Sprouty Signaling in Glioma

Abstract: Gliomas are primary brain tumors with high mortality and heterogeneous biology that is insufficiently understood. In this study, we performed a systematic analysis of the intrinsic organization of complex glioma transcriptome to gain deeper knowledge of the tumor biology. Gene coexpression relationships were explored in 790 glioma samples from 5 published patient cohorts treated at different institutions. We identified 20 coexpression modules that were common to all the data sets and associated with proliferat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 40 publications
3
72
0
Order By: Relevance
“…Unfortunately, the underlying molecular mechanisms of unlimited proliferation and progressive local invasion remain obscure. Previous work has demonstrated that GBM frequently harbors mutations that activate EGFR and launch downstream signaling pathways, including the PI3K/ATK and Ras/Raf/MEK/ERK pathways (6,8,32). However, EGFR-Ras or PI3K mutations alone are not sufficient to transform glial cells; instead, multiple mutations that coactivate the EGFR-Ras and PI3K/Akt pathways are necessary to induce glioma (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the underlying molecular mechanisms of unlimited proliferation and progressive local invasion remain obscure. Previous work has demonstrated that GBM frequently harbors mutations that activate EGFR and launch downstream signaling pathways, including the PI3K/ATK and Ras/Raf/MEK/ERK pathways (6,8,32). However, EGFR-Ras or PI3K mutations alone are not sufficient to transform glial cells; instead, multiple mutations that coactivate the EGFR-Ras and PI3K/Akt pathways are necessary to induce glioma (33).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, EGFR plays a vital role in various aspects of malignancy, particularly in tumor cell proliferation, survival and metastasis (4,5). Glioma-associated EGFR mutant forms show constitutive kinase activity that chronically stimulates Ras signaling to drive cell cycle progression and also activates the PI3K/AKT pathway to promote cellular proliferation and migration (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…14 Ivliev et al also identified transcriptional modules related to proastrocytic differentiation and sprout signaling in gliomas. 16 In our study, among the 23 coexpression modules, we identified one that was strongly associated with tumorigenesis and could be considered an oncogenic module. This module contains 356 genes and is enriched in glycoprotein/membrane/blood vessel development and cell migration.…”
Section: 40mentioning
confidence: 77%
“…2,6,45 The WGCNA approach has been widely used to identify potential oncogenic coexpression modules and predict the molecular targets and prognosis markers. 14,16,38,55,58 For instance, Horvath et al have successfully identified the gene ASPM as a molecular target for glioblastoma, another primary brain tumor. 14 Ivliev et al also identified transcriptional modules related to proastrocytic differentiation and sprout signaling in gliomas.…”
Section: 40mentioning
confidence: 99%
“…Note Analysis of a glioma dataset containing expression data from 276 tumor samples revealed that SPROUTY (SPRY1, SPRY2, and SPRY4) genes are coordinately upregulated in EGFR amplified gliomas (Ivliev et al, 2010). The role and significance of SPRY1 in glioma has not been functionally addressed.…”
Section: Gliomamentioning
confidence: 99%